aBVA Procedure by Uniportal Video-Assisted Thoracoscopic Surgery for Right Upper Peripheral Lung Cancer: A Randomized Trial - Wang, Kaiying; Zhang, Jian; Li, Jianglun; Liu, Langbo; Tang, Zhongben; Du, Xiaojun (Frontiers in Oncology, 2022)
Objective: To distinguish the optimal dividing order of the anatomic pulmonary resection under uniportal Video-Assisted Thoracoscopic Surgery (uni-VATS) for patients with right upper peripheral lung cancer. Methods: Patients met the eligibility and exclusion criteria were randomly allocated into aBVA group and VAB group. In aBVA group, the surgical procedure proceeded from the posterior to the anterior (from the deeper to the superficial site). While, in VAB group, the dissection orders were: vein first followed by arterial branches, and then bronchus. Clinical data was collected and analyzed. Results: 60 patients were randomly allocated into aBVA group (n=30) and VAB group (n=30). The operation time in aBVA group (230.500±68.360) was significant less than that in VAB group (305.600±107.821) (P=0.01).The blood loss in aBVA group (104.000±70.935) was significant less than that in VAB group (391.000±625.175) (P=0.01). 2 patients in the VAB group received conversion to a 2-portal VATS. The numbers of lymph nodes (13.367±5.436 vs. 10.333±7.279, P=0.072) and lymph node stations (5.067±1.574 vs. 4.467±2.345 , P=0.567) removed were comparable between the two groups. The differences of days of postoperative drainage tube stay (5.033±3.113 vs. 6.467±4.447, P=0.278) and hospital stay (8.233±3.390 vs. 9.433±4.523, P=0.361) were not significant between the two groups either. Conclusion: Comparing to VBA procedure, aBVA is easier for patients with right upper peripheral lung cancer who received uni-VATS lobectomy.